Alternative methods for functional assessment of intermediate coronary lesions - Zaleska, Martyna (Cardiol J, 2020)
Wire-based fractional flow reserve (FFR) is a diagnostic tool used to evaluate the ischemic burden of coronary lesions. Large-scale studies have shown that FFR-guided revascularization is associated with better clinical outcomes. However, wide adoption of this technology is limited due to the considerable cost, additional time needed for set-up and performance of the measurement as well as the invasiveness of the procedure which requires pressure wire placement across the lesion into the distal segment of the coronary artery. To overcome these limitations new, promising, and less-/non-invasive methods were developed. These methods are based on computational fluid dynamics analysis and three-dimensional lumen reconstruction. The aim of this paper is to review scientific evidence supporting the clinical safety and efficacy of these techniques, such as instantaneous wave-free ratio, quantitative flow ratio and FFR calculated from computed tomographic angiography.